ANALYSIS OF STUDENTS’ MISCONCEPTION PROFILE ON HUMAN RESPIRATORY SYSTEM MATERIAL USING FOUR-TIER DIAGNOSTIC TEST - Utamy, Vyra Garmyta; Rosdiana, Laily (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
In science subjects, the material of the human respiratory system is widely misconceived by students. These students' misconceptions need to be identified because it may cause students to have difficulty connecting old concepts with new concepts. Based on this, a study was conducted to determine the students' misconception profile on the material of the respiratory system. This research method uses descriptive methods with a quantitative approach. This study involved 90 students of class VIII in Driyorejo District. The instrument used in this study was a four-tier diagnostic test with total 20 questions related to human respiratory system.. The results show that students in junior high schools in Driyorejo District experience 52% misconceptions which is categorized as moderate. Misconceptions occur in all concepts of respiratory system material with the highest percentage of misconceptions in the concept of respiratory frequency which is misconceived by 62% of SMP 5 YPM students.